The ... ageing report (Publication Office of the European Union, 2023)
The forthcoming 2024 Ageing Report will provide long-term projections for public expenditure on pensions, healthcare, long-term care and education in the European Union up to 2070. These budgetary projections build on the macroeconomic assumptions and methodologies described in this report. The 2024 Ageing Report will be the eighth edition. Publication is scheduled for spring 2024.
10.2765/960576
Keywords: Graue Literatur; population forecast; economic forecasting; long-term forecast; population ageing; public finance; labour force; non-working population; pension scheme; health expenditure; unemployment; EU expenditure; macroeconomics; EU Member State; report